EXPLORING ISLAMIC FINTECH: A BIBLIOMETRIC APPROACH - Mohammad Irfan; Sylva Alif Rusmita (Universitas Airlangga, 2023)
Introduction: In recent years, Islamic Fintech and bibliometric analysis in general have drawn more attention in the finance literature. In this study, all papers indexed in the Dimensions database that cover the wide topic of Fintech and Islamic Fintech from 2017 to 2023 are examined using bibliometric analytical tools. Methods: The authors discovered 675 papers that met the set function, subject, and criteria requirements. The papers' publishing by knowledge area, annual study output, national contribution, author count, and most prestigious journals were all analysed. The co-occurrence of keywords and document citations was visually analysed using the VOS viewer. Filter the data set from